Culture as politics : selected writings of Christopher Caudwell - Caudwell, Christopher, 1907-1937 (Monthly Review Press, 2018)
"Selected essays by Christopher Caudwell, on culture, psychology, and capitalism. Material drawn from Caudwell's previous book, "Illusion and Reality, Studies in a Dying Culture" and his essay, "Heredity and Development.""--